2008
DOI: 10.1128/aem.01663-07
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Ripening Starter Microorganisms Inoculated into Cheese Milk Do Not Successfully Establish Themselves in the Resident Microbial Ripening Consortia of a South German Red Smear Cheese

Abstract: Production of smear-ripened cheese critically depends on the surface growth of multispecies microbial consortia comprising bacteria and yeasts. These microorganisms often originate from the cheese-making facility and, over many years, have developed into rather stable, dairy-specific associations. While commercial smear starters are frequently used, it is unclear to what degree these are able to establish successfully within the resident microbial consortia. Thus, the fate of the smear starters of a German Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 34 publications
(63 reference statements)
9
50
0
Order By: Relevance
“…FT-IR spectroscopy for typing these lactic acid bacteria below the species level is demonstrated by our data, as has already been done for coryneform bacteria by Goerges et al (2008).…”
Section: S J Schmidt and Otherssupporting
confidence: 58%
“…FT-IR spectroscopy for typing these lactic acid bacteria below the species level is demonstrated by our data, as has already been done for coryneform bacteria by Goerges et al (2008).…”
Section: S J Schmidt and Otherssupporting
confidence: 58%
“…Both Candida sp and, in particular, Saccharomyces sp are routinely used in the brewing and baking industry; Galactomyces sp are routinely found in cheese microbial consortia where they are used in starter cultures (Goerges et al, 2008); and Galactomyces geotrichum has also been identified as an agent in soft drinks spoilage (Ancasi et al, 2006). As such, when fermented foods and beverages or food containing eukaryotic species are consumed on a continuous basis, they provide ready inocula for the host.…”
Section: Resultsmentioning
confidence: 99%
“…However, two morphologically different types of this mould were found in the samples. One colony had a turquoise-to blue-coloured surface and was present in all batches, and the other had a light green and fluffy appearance and was present in half of the batches (Goerges et al, 2008).…”
Section: Dairy and Alcohol Industriesmentioning
confidence: 99%
“…The most frequently described sources of G. geotrichum isolation are summarized in Figure 1. The majority of publications concerning the G. geotrichum mould are related to its presence in the dairy industry, especially in cheeses (Binetti et al, 2013;Chebeňová-Turcovská et al, 2011;Flores--Magallón et al, 2011;Goerges et al, 2008;Majcher et al, 2014;Sadecka et al, 2016;. This mould belongs to secondary microflora and is able to survive in ripening cheese where the pH is low and where water activity and salt concentration are high (Binetti et al, 2013).…”
Section: Dairy and Alcohol Industriesmentioning
confidence: 99%
See 1 more Smart Citation